MORPHOLOGICAL CHANGES IN THE LIVER OF OFFSPRING 3 -30 DAYS BORN TO MOTHERS IN A STATE OF EXPERIMENTAL STRESS - Nortaev A.B.,; Abdudjalilova Y.H.,; Raxmonberdiyev M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article tells about the universal non-specific neurogormonal reaction of the body in the form of stress, an injury manifested by increased resistance of the body, or the tension of non-specific adaptation mechanisms in response to a signal that threatens the life or well-being of the body.